Incidence of catheter-related bloodstream infections after removal of peripherally inserted central catheters in preterm neonates - Tomar, Rampal Singh; Gupta, Ashish Kr; Khan, I. D. (International Journal of Contemporary Pediatrics, 2020)
Background: Peripherally inserted central catheter (PICC) have become essential for a safe and reliable long term venous access in all neonatal intensive care units (NICU) for providing long term intravenous fluids and medications. However, they associated with central line blood stream infections (CRBSI) infections and it is postulated that this risk is more on during their removal but the true incidence is not known. The objective was to evaluate the incidence and identify risk factors associated with CRBSI following the PICC removal in preterm neonates. Methods: This was a retrospective cohort study was done on <37 weeks premature neonates. Data included patient particulars, location of PICC placement, days of PICC, antibiotics and TPN through PICC, infections noted during or within 48 hours of PICC removal. Results: A total of 238 PICC removals in 215 neonates were analysed which did not show a significant difference in the prevalence of CRBSI within 48 hours of PICC removal. However, there was an increase in odds for sepsis following PICC removal in less than 29 weeks gestation and if it was not used for antibiotic infusion for more than 48 hours preceding its removal. Conclusions: This study does not support the use of prophylactic antibiotics during PICC removal in neonates as there was no increase in the incidence of CRBSI following PICC removal. However, they may have a role in very low gestation age, low birth weight infants who have not recently received antibiotics prior to PICC removal.